The Effect of Direct Interaction Strategy in Teaching Reading Comprehension at the Tenth Grade of SMA Negeri Taekas in the Academic Year 2024/2025 - Sengkoen, Maria Gradiana; Misa, Mikhael; Seran, Yanuarius (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2025)
This study aimed to examine the effect of the Direct Interaction Strategy on teaching reading comprehension of narrative texts at the tenth grade of SMA Negeri Taekas in the academic year 2024/2025. The research employed a quasi-experimental design with two groups: an experimental class that received instruction using the Direct Interaction Strategy and a control class that was taught using conventional teaching methods. Data were collected using pre-tests and post-tests to measure students' reading comprehension before and after the intervention.The findings reveal a significant improvement in the reading comprehension scores of the experimental class compared to the control class. The experimental group showed an increase from an average pre-test score of 43.6% (categorized as